Stock Market Development and Economic Growth: Empirical Evidence from Nepal - Regmi, Udaya Raj (Administration and Management Review, 2012)
This article examines causal relationship between stock market development and economic growth in Nepal for the period 1994-2011, using unit root test, co-integration, and vector error correction models and developing NEPSE composite index as an indicator of stock market development. The finding suggests that stock market development has significantly contributed to the economic growth in Nepal. In this perspective, a refined policy measures should be adopted to strengthen and improve the role of stock market in order to expedite and maintain the strong growth of the economy. Administration and Management Review Vol. 24, No. 1, January, 2012, Page 1-28